The Effect of Tangible and Reability on Customer Satisfaction of Bank Syariah Indonesia (BSI) at Thursina Hospital in Duri City - Anis Mahmudah Dariati (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2022)
This study aims to determine the effect of tangible and reability on customer satisfaction at bank syariah Indonesia (BSI) at thursina hospital in duri city. This study uses quantitative associative causal relationship (cause and effect). The population of this study are BSI customers at tge hospital. Thursina as many as 111 customers. The sampling technique used purposive sampling, amounting to 87 respondents. Data collection techniques in this study used questionnaires and literature (literature study). The data analysis method uses multiple linear regression analysis with IBM SPSS Statistics Version 22 software. The results of this study indicate that tangible has a positive effect on BSI customer satisfaction in thursina hospital with sig 0,0030,05. Meanwhile, reliability has a negative and significant effect on customer satisfaction with a sig 0,0130,05.